Stunting education using the brainstorming method to increase mother literacy in Banyumas Regency - Ika Pantiawati; Widya Ratna Wulan; Evina Widianawati; Tiara Fani (Community Empowerment, 2023)
The limited information obtained by mothers is one of the obstacles in producing correct stunting information. This community service aims to increase mother literacy about stunting toddlers in the stunting locus village, Banyumas Regency using the brainstorming method. The stages of the program start from preparation, pre-test, giving material and post-test. The results of the pre-test and post-test showed that mothers' knowledge about stunting increased by 37% compared to before assistance. Knowledge that has increased the most is about how to handle stunting in toddlers (79%). However, there is no increase in knowledge about how to vary food that is good for stunting toddlers. Stunting education assistance activities using the brainstorming method need to be carried out routinely for mothers of stunting toddlers to increase their knowledge and change the behavior in handling stunting in their toddlers so that the prevalence of stunting can decrease.